Chemical exposure levels in printing workers with cholangiocarcinoma (second report). Issue 3 (14th July 2015) - Yamada, Kenichi; Kumagai, Shinji; Endo, Ginji
Abstract : Chemical exposure levels in printing workers with cholangiocarcinoma (second report): Kenichi Yamada, et al . Occupational Health Research and Development Center, Japan Industrial Safety and Health Association Objective: In several Japanese printing plants, printing workers have suffered from cholangiocarcinoma. 1, 2‐dichloropropane (1, 2‐DCP) is considered to be a causative agent, and whether or not other chemicals also contribute to the development of this disease has not been conclusively determined. This study aimed to identify the chemicals used by seven printing workers who developed cholangiocarcinoma, as well as to estimate the levels of chemical exposure among them. Methods: Information was obtained from the Ministry of Health, Labour and Welfare, Japan, to identify chemicals used by printing workers who developed cholangiocarcinoma and to estimate chemical exposure concentrations. Working environment concentrations of the chemicals in the printing rooms were estimated using a well‐mixed model, and exposure concentrations during the ink removal operation were estimated using a near‐field and far‐field model. Shift time‐weighted averages of exposure concentrations were also calculated. Results: Four of the seven printing workers were exposed to both 1, 2‐DCP and dichloromethane (DCM). The estimated maximum exposure concentrations for each of the four workers were 230 to 420 ppm for 1, 2‐DCP and 58 to 720 ppm for DCM, and the estimated shift average exposure concentrations were 0 to 210 ppm for 1, 2‐DCP and 15 to 270 ppm for DCM. The remaining three workers were exposed to DCM but not 1, 2‐DCP. The estimated maximum exposure concentrations of DCM for each of the three workers were 600 to 1, 300 ppm, and the estimated shift average exposure concentrations were 84 to 440 ppm. Conclusions: Our findings suggest that DCM may contribute to the development of cholangiocarcinoma in humans.